A TWO-PHASE GAS-LIQUID FLUID FLOW - Belikov V.T. (My University, 1999)
A quantitative description is given for the flow of a two-phase fluid consisting of the liquid with bubbles of dissolved gas. The general formulation of the problem is tested for the case of a steady-state flow of an aqueous fluid containing dissolved carbon dioxide.